The Impact of Return on Assets and Current Ratio on Shoe Company Valuation From 2018 To 2022 - Ainani Yunda Fitria; Robbi Saepul Rahman; Galih Putra Prawiranegara (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2026)
This study aims to determine and analyze Return on Assets at a certain shoe company, Current Ratio at the same entity, the valuation (PER) of the shoe company, and how Return on Assets and Current Ratio impact this valuation. The research introduces a novel perspective by focusing specifically on this company's financial metrics, an area that has not been widely explored in existing literature. The research adopts a quantitative approach through multiple linear regression analysis. Data collection comes from the Financial Statements and Income Statements of the shoe company. The investigation emphasizes the relationship between Return on Assets, Current Ratio, and valuation. To assess this influence, the study utilizes the coefficient of determination, while employing Ms. Excel and SPSS version 25 for Windows for data analysis. Findings indicate that, according to t-test results, Return on Assets and Current Ratio positively and significantly affect valuation. Furthermore, the f-test confirms that these two metrics collectively have a positive and significant impact on valuation. The coefficient of determination shows that these indicators significantly influence the dependent variable, while the remaining factors relate to other aspects not covered in this research. This study provides practical insights for stakeholders in the footwear industry, shedding light on essential factors that can drive company performance and investment decisions.